THE IMPACT OF AN ADDITIONAL WEEK PROGRAM AS A PROTECTION INDICATOR IN WOMEN VOLLEYBALL - Nora Deda; Artan Kalaja (European Scientific Journal, ESJ, 2015)
Volleyball is a sport that is continuously modernized and developed to coincide with the overall development of the society. Among the most defining elements of modern volleyball, protection is of immense importance. Its basic elements include block, waiting for the ball, and waiting for the opponent's reactions to setbacks. Due to the speed and high bodily altitude of jumping in women and men’s volleyball, it is very necessary to acquire an excellent technical and physical preparation. Specifically, this is in a view to meet the specifics of this game. In this study, we were able to prove that the available time for training in protective exercises is not enough in the actual practice of female volleyball in Albania. It must be increased not only quantitatively, but also on the composition of the training process that is dedicated to the technical tactical indicators of the key elements of the defense. Two female volleyball teams were involved in the experiment. One team was treated with an additional training program of 90 minutes per week for a period of 12 weeks. Also, the other team continued normal training process being treated as the control group. Each week, both teams held match training between themselves, through a clear procedure. During the training, the collective parameters of block, first ball reception, and reception to setbacks was highlighted. Results of the study show that the quantity and quality increase of training for protective actions is a more efficient way to improve athletic performance in women's volleyball.